2011
DOI: 10.1007/s12011-011-9196-5
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Mineral Sources Altered Lipid and Antioxidant Profiles in Broiler Breeders and Posthatch Growth of Their Offsprings

Abstract: The aim of this study was to investigate the influence of mineral sources on broiler breeders and their offsprings. Broiler breeding hens were fed with diets containing either organic or inorganic trace minerals at equal levels, i.e., (1) control group was fed with basal diet supplemented with inorganic trace minerals; (2) OZ group was fed with organic Zn instead of sulfate; and (3) OTM group was fed with organic Cu, Mn, Zn, and Se instead of inorganic sources. Results indicated that OTM supplementation decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…As our results indicate improvements in egg quality, the increased hatching rate, the improved fertilization rate, and the healthy chick rate can also be associated with the egg quality and the increased eggshell strength and density, which prevent pathogenic microorganisms from entering the eggs. Moreover, YC also contains a large amount of trace elements, such as selenium and zinc that improve embryonic and early postnatal development of the aged layer (Hostetler et al, 2003;Sun et al, 2012). A previous study has shown that adding yeast bioactives significantly improves the level of IgA in the egg yolk (Lu et al, 2019), resulting in enhanced chick immunity and improved reproductive performance of the aged layers.…”
Section: Discussionmentioning
confidence: 99%
“…As our results indicate improvements in egg quality, the increased hatching rate, the improved fertilization rate, and the healthy chick rate can also be associated with the egg quality and the increased eggshell strength and density, which prevent pathogenic microorganisms from entering the eggs. Moreover, YC also contains a large amount of trace elements, such as selenium and zinc that improve embryonic and early postnatal development of the aged layer (Hostetler et al, 2003;Sun et al, 2012). A previous study has shown that adding yeast bioactives significantly improves the level of IgA in the egg yolk (Lu et al, 2019), resulting in enhanced chick immunity and improved reproductive performance of the aged layers.…”
Section: Discussionmentioning
confidence: 99%
“…It plays an important role in calcium and phosphorus metabolism by acting on the absorption and recycling of calcium in the intestine ( Berridge et al., 2003 ). Consequently, it can increase the concentration of circulating calcium for egg production ( Sun et al., 2012 ), positively influencing the laying rate, shell quality, embryonic development, bone tissue growth, and hatching ( Saunders-Blade and Kover ).…”
Section: Introductionmentioning
confidence: 99%
“…Zn as a component of Cu/Zn-SOD protects proteins and enzymes from radical attacks, and second, Zn prevents the free radicals' formation from other metals (Fe and Cu) ( Kucuk, 2008 ). It is also demonstrated in previous studies that broiler breeders showed better antioxidant status by feeding organic Zn as compared to inorganic form ( Zhang et al., 2017 ) and reduced the level of serum and liver MDA ( Sahin et al., 2005 , Sun et al., 2012 ). In line with the present findings, it is suggested by other studies that broiler breeders show better antioxidant status by feeding OTM compared with ITM ( Wang et al., 2019a ).…”
Section: Discussionmentioning
confidence: 68%